Horizontal links within and between paradigms - Smirnova, Elena (My University, 2021)
This paper deals with the constructional network of reported directive speech acts in German. It addresses two aspects of modality and constructions by relating directly to questions raised in the introduction to this volume: the notion of the paradigm in Construction Grammar on the one hand and the nature of the links within the constructional network model on the other. By investigating the network of syntactic constructions of reported directives in German, the paper focuses on the modelling of two types of horizonal paradigmatic links between these constructions: the links between allostructions and the links between paradigmatic choices. On the conceptual level, the paper argues that these two types of paradigmatic links constitute two different types of horizontal links in the network. On the empirical level, the study demonstrates how these horizontal links manifest themselves in the corpus data.